Identifying Breast Cancer Care Quality Measures for a Cancer Facility in Rural Sub-Saharan Africa: Results of a Systematic Literature Review and Modified Delphi Process - Lydia E. Pace; Lauren E. Schleimer; Cyprien Shyirambere; André Ilbawi; Jean Marie Vianney Dusengimana; Jean Bosco Bigirimana; Francois Regis Uwizeye; Mary Chamberlin; Yeonsoo Sara Lee; Lawrence N. Shulman; Susan Troyan; Benjamin O. Anderson; et al. (JCO Global Oncology, 2020)
PURPOSEThe burden of cancer is growing in low- and middle-income countries (LMICs), including sub-Saharan Africa. Ensuring the delivery of high-quality cancer care in such regions is a pressing concern. There is a need for strategies to identify meaningful and relevant quality measures that are applicable to and usable for quality measurement and improvement in resource-constrained settings.METHODSTo identify quality measures for breast cancer care at Butaro Cancer Center of Excellence (BCCOE) in Rwanda, we used a modified Delphi process engaging two panels of experts, one with expertise in breast cancer evidence and measures used in high-income countries and one with expertise in cancer care delivery in Rwanda.RESULTSOur systematic review of the literature yielded no publications describing breast cancer quality measures developed in a low-income country, but it did provide 40 quality measures, which we adapted for relevance to our setting. After two surveys, one conference call, and one in-person meeting, 17 measures were identified as relevant to pathology, staging and treatment planning, surgery, chemotherapy, endocrine therapy, palliative care, and retention in care. Successes of the process included participation by a diverse set of global experts and engagement of the BCCOE community in quality measurement and improvement. Anticipated challenges include the need to continually refine these measures as resources, protocols, and measurement capacity rapidly evolve in Rwanda.CONCLUSIONA modified Delphi process engaging both global and local expertise was a promising strategy to identify quality measures for breast cancer in Rwanda. The process and resulting measures may also be relevant for other LMIC cancer facilities. Next steps include validation of these measures in a retrospective cohort of patients with breast cancer.